2017
DOI: 10.1248/bpb.b16-00882
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Ameliorates Renal Fibrosis and Expression of Endothelial Cell Transition Markers in Rats of Isoproterenol-Induced Heart Failure

Abstract: There may be cardio-renal interactions in rats of isoproterenol-induced heart failure, which may be associated with renal fibrosis and endothelial-to-mesenchymal transition (EndMT). Since its discovery, relaxin (RLX) which was regarded as a reproductive hormone for a long time, is recently considered an effective antifibrotic hormone in cardiac and renal fibrosis. We studied whether RLX diminished renal fibrosis in rats of isoproterenol (Iso)-induced heart failure and investigated the mechanism. Fifty male Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Recent studies showed that serelaxin inhibits EndMT within the heart and kidney of isoprenaline-induced cardiomyopathy in rodents (Cai et al, 2017;Zheng et al, 2017). Zhou et al found that serelaxin improves cardiac function in rats with myocardial fibrosis, by reducing EndMT and interstitial collagens I and III, while increasing the microvascular density of the heart (Zhou et al, 2015).…”
Section: Relaxin Effects On Endothelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…Recent studies showed that serelaxin inhibits EndMT within the heart and kidney of isoprenaline-induced cardiomyopathy in rodents (Cai et al, 2017;Zheng et al, 2017). Zhou et al found that serelaxin improves cardiac function in rats with myocardial fibrosis, by reducing EndMT and interstitial collagens I and III, while increasing the microvascular density of the heart (Zhou et al, 2015).…”
Section: Relaxin Effects On Endothelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…A total of 40 signaling pathways were identified. In the most significantly altered signaling pathway in this study, fibrosis was reported in previous studies to be involved in the ‘Hedgehog signaling pathway’ ( 35 37 ), ‘ABC transporters’ ( 38 ), ‘ErbB signaling pathway’ ( 39 , 40 ), ‘cAMP signaling pathway’ ( 41 , 42 ), ‘Relaxin signaling pathway’ ( 43 , 44 ), ‘Ras signaling pathway’ ( 45 , 46 ) and ‘PI3K-Akt signaling pathway’ ( 47 , 48 ). Additionally, six ECM-associated pathways were directly associated with renal fibrosis.…”
Section: Discussionmentioning
confidence: 52%
“…4 week post-MI, animals presented renal fibrosis, oxidative stress and inflammation. We show for the first time that these alterations were Several studies have demonstrated that MI is associated with renal damage (24,25). ER is an organelle essential for protein biosynthesis and post-translational modifications, which is very sensitive to unfolded and misfolded proteins in the lumen of ER.…”
Section: Discussionmentioning
confidence: 65%